[OA218] Dose monitoring for physicians' lens in Catheterization Lab: Intercenter survey. (August 2018) - Betti, Margherita; Belli, Giacomo; Bernardi, Luca; Bicchi, Sara; Busoni, Simone; Fedele, David; Mazzoni, Lorenzo Nicola; Vaiano, Angela; Quattrocchi, Mariagrazia; Taddeucci, Adriana; Gori, Cesare; Fedeli, Luca; et al.
Abstract : Purpose: The immediate consequence of the new equivalent dose limit for the lens of the eye was a change in the international basic safety standards (BSS) and in the European BSS and the adoption of new limit. For the Catheter Laboratory Procedure, available literature mentions a poor correlation between chest dose measurements and eye lens doses. Aim of the study is to evaluate, if there is any, the correlation between clinical and technical parameters and operator lens dose. Methods: Operators, who have used ceiling suspended screen, were monitored throughout thermoluminescence dosimeters (TLDs). The accredited laboratory pass EURADOS intercomparison on Eye Lens in 2016, using TLD calibrated in Hp(0.07), therefore also Hp(0.07) dosimeters are suitable for this application. Chest TLD dosimeter were placed under the lead apron at chest level, hand TLD on the bracelet and the lens TLD was positioned under the shielded glasses. Patient dose values (kerma area product), clinical and technical parameters, as number and type of procedures, were recorded and analyzed. Results: The lens dose for main operator in Catheterization Lab of the first 3 centres enrolled are reported. As expected, hands dose depends on the type of procedure performed. Despite this, it is possible to find a weak correlation between the hands dose and the total number of procedures performed by the operator. The chest dose seems to be a completely unrelated parameter with the lens dose. The lens dose does not correlate with the parameters analyzed. Conclusions: Lens dose monitor is an extremely complex features. The position of the dosimeter, the type of procedure, the operator experience, and also clinical condition of the patient strongly affect that parameter. Chest and bracelet dosimeters appear not to be adequate for efficient lens dose monitoring.